52-4x=12-18x

Simple and best practice solution for 52-4x=12-18x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 52-4x=12-18x equation:


Simplifying
52 + -4x = 12 + -18x

Solving
52 + -4x = 12 + -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
52 + -4x + 18x = 12 + -18x + 18x

Combine like terms: -4x + 18x = 14x
52 + 14x = 12 + -18x + 18x

Combine like terms: -18x + 18x = 0
52 + 14x = 12 + 0
52 + 14x = 12

Add '-52' to each side of the equation.
52 + -52 + 14x = 12 + -52

Combine like terms: 52 + -52 = 0
0 + 14x = 12 + -52
14x = 12 + -52

Combine like terms: 12 + -52 = -40
14x = -40

Divide each side by '14'.
x = -2.857142857

Simplifying
x = -2.857142857

See similar equations:

| 0w=23 | | 3(2x-2)-3=3(x-5)+24 | | -9x+2=65 | | R(q)=-1.5q+140 | | 2y-8=14y+64 | | 2x^3-486x=0 | | 7(3x-4)=37 | | 9m^2=1 | | E=200+0.8(Y-0)+200+0.1Y+100+100-100-0.15Y | | 4n-13=-1 | | 7(5y-4)-(9y+3)= | | 23+x-4x=56-3x | | 6x+3(-2x+4)= | | 36-2(6-2)= | | -40=-4(y+3) | | 4+y=21 | | 5(2x+4)=(4x+1) | | 8+z=21 | | 6/15-3/10 | | 4a+3a-80=2a+a+4 | | x+2(x+2)=4(3x-2) | | X+X=9+7 | | 58=2/3w= | | 100m=-6m | | 0.75x=10+0.50x | | 2y-1=31 | | 100m=-6 | | 4x+44y=-12 | | 29-5x=11 | | (3x-12)=90 | | -23=-8+3u | | 4(6x+7)=64 |

Equations solver categories